KUALITAS INFROMASI AKUNTANSI DAN TINGKAT PENERIMAAN DANA ZAKAT PADA LEMBAGA AMIL ZAKAT DI KOTA MEDAN - Sri Rahayu (Jurnal Investasi Islam, 2019)
Zakat is very potential as an effective means to empower the economy of the people. If this potential is optimally explored from the entire Islamic community and managed well with trust management and high professionalism, it will realize a large amount of funds that can be utilized to overcome the economy of the people. The purpose of this study was to test and analyze empirically the effect of the quality of accounting information on the level of receipt of zakat funds at the Amil Zakat Institution in Medan City. The sample in this study used the saturated sample method. Data were analyzed using linear regression analysis. The results of this study stated that the quality of accounting information has a positive effect on the level of receipt of zakat funds.